The effect of primary care fellowship training on career satisfaction, happiness and perceived stress. Issue 1065 (24th April 2014) - Duffrin, Christopher; Larsen, Lars
Abstract: Purpose: This study was designed to measure the impact of primary care fellowship training on the subsequent happiness, career satisfaction and perceived stress levels of fellowship-trained physicians as compared to a general population of Family Medicine physicians in North Carolina. Methods: A written survey instrument was completed by fellowship graduates of the Brody School of Medicine (n=53) and general population of Family Medicine physicians in North Carolina (n=203) in 2011. The survey included general demographic and practice variables, and validated psychological scales on subjective happiness, satisfaction with life, and perceived stress. Results: Fellowship graduates (n=50), and non-fellowship graduates (n=203), exhibited similar levels of satisfaction with life (fellows=27.36 SD 5.45, FM physicians=26.91, SD 5.99 on a 5–35 scale), statistically higher levels of perceived stress (fellows=5.92, SD 3.03, FM physicians=4.98, SD 2.70 on a 0–16 scale), and significantly higher levels of subjective happiness (fellows=5.61SD 83, FM physician=4.75 SD 1.00 on a 1–7 scale). Female fellow response was significantly higher on the Satisfaction with Life and Subjective Happiness Scores, and lower on the Perceived Stress Scale. Male fellowship graduates presented with a reverse relationship, with higher perceived stress and lower satisfaction with life and subjective happiness. Conclusions: Fellowship training exhibited a positive psychological effect on the graduate respondents versus the general physician population. Scores on various well-being scales were higher than the general Family Medicine physician population as a whole, although stress levels were also higher. Female physicians seem to garner a much larger gain in satisfaction than male fellowship graduates, who score slightly worse than the general family medicine population on the satisfaction with life and Perceived Stress Scales.